Proceedings of the 4th Annual International Seminar on Transformative Education and Educational Leadership (AISTEEL 2019) 2019
DOI: 10.2991/aisteel-19.2019.39
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Contextual-Inquiry Based Worksheet in Water Microbiology Material for Students’ Scientific Process Skills in FMIPA UNIMED

Abstract: This study aimed to determine the effect of the application of contextual-inquiry based worksheets on students' scientific process skills in the sixth semester of biology education undergraduate students in FMIPA UNIMED. This study used a quasi-experimental method with one dependent variable with 3 (three) classes as sample which are determined by random class. Regular class A got the treatment of applying contextual inquiry worksheets, Extension class A got the treatment of applying PBMP worksheets (pemberday… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…According to (Hasruddin et al, 2018) explained that science process skills that involve cognitive and intellectual learning will achieve good learning outcomes. According to (Kesumawati & Sudibyo, 2019) suggested that there is an influence on the application of contextual inquiry and empowerment of thinking through questions on science process skills. According to (Malik, 2016), the need for teachers to conduct learning and approach students' science process skills to help student knowledge.…”
Section: Figurementioning
confidence: 99%
“…According to (Hasruddin et al, 2018) explained that science process skills that involve cognitive and intellectual learning will achieve good learning outcomes. According to (Kesumawati & Sudibyo, 2019) suggested that there is an influence on the application of contextual inquiry and empowerment of thinking through questions on science process skills. According to (Malik, 2016), the need for teachers to conduct learning and approach students' science process skills to help student knowledge.…”
Section: Figurementioning
confidence: 99%